PENGARUH METODE BERMAIN JAWABAN TERHADAP MOTIVASI BELAJAR PPKn SISWA KELAS X IPS SMA NEGERI 9 PEKANBARU - Irma Novita Desi; Gimin Gimin; Supentri Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to determine the effect of using Bermain Jawaban learning method toward social students motivation in learning PPKn at SMA Negeri 9 Pekanbaru. This study aims to determine the effect of of using Bermain Jawaban learning method toward students’ motivation in learning PPKn at SMA Negeri 9 Pekanbaru.This research was a quantitative descriptive study that was experimental.Population in this study were social students of class X IPS SMA Negeri 9 Pekanbaru. The sample in this research was taken based on "Multi Stage Random Sampling" technique. Where the class taken into the sample was the students of class X IPS 2 (experimental class) who were given the Bermain Jawaban learning method, and class X IPS 1 (control class).Taken randomly were students who were given the conventional method. Then data analysis by using homogeneity test and "t" test. Based on the result of research indicated that there wasan effect of learning motivation between student who using Bermain Jawaban learning method and conventional method in SMA Negeri 9 Pekanbaru (>).Where there was an average increase toward motivation in learning PPKn of experimental class  from 22,8 to 24,9 and the average of PPKn learning motivation of control class from 16,3 to 20,6. Thus the hypothesis which reads that there is an effect of using Bermain Jawaban learning method toward learning motivation of PPKn student at SMA Negeri 9 Pekanbaru, can be accepted. Key Words : Effect, Bermain Jawaban, Motivation